Glycemia in Acute Stroke II study: a call to improve post‐stroke hyperglycemia management in clinical practice. (14th July 2017) - Fuentes, B.; Sanz‐Cuesta, B. E.; Gutiérrez‐Fernández, M.; Martínez‐Sánchez, P.; Lisbona, A.; Madero‐Jarabo, R.; Delgado‐Mederos, R.; Gállego‐Cullere, J.; Rodríguez‐Yáñez, M.; Martínez‐Zabaleta, M.; Freijo, M.; Alonso de Leciñana, M.; et al.
Abstract : Background and purpose: The aim of the study was to analyze the effect of conventional glucose management, which aimed to maintain glucose levels <155 mg/dL (8.5 mmol/L), on glucose control and the outcomes of patients with acute ischaemic stroke (IS) in a clinical practice setting. Methods: This was a multicenter, prospective cohort study of patients with acute IS. Patients were classified into four groups based on their initial 48‐h capillary glucose levels and the administration of and response to corrective treatment: (i) untreated and maximum glucose levels <155 mg/dL (8.5 mmol/L) within the first 48 h; (ii) treated and good responders [glucose levels persistently <155 mg/dL (8.5 mmol/L)]; (iii) treated and non‐responders [any glucose values ≥155 mg/dL (8.5 mmol/L) during the 24 h after the start of corrective treatment]; and (iv) untreated with any glucose value ≥155 mg/dL (8.5 mmol/L). The primary outcome was death or dependence at 3 months (blinded rater). Results: A total of 213 patients were included. Ninety‐seven (45.5%) patients developed glucose levels ≥155 mg/dL (8.5 mmol/L), 69 (71.1%) underwent corrective treatment and 31 patients underwent no corrective treatment at the physician's discretion [28 of whom had isolated values ≥155 mg/dL (8.5 mmol/L)]. Only 11 (16%) patients responded to conventional treatment, whereas 58 (84%) patients were non‐responsive. Non‐responders showed a twofold higher risk of death or dependence at 3 months (odds ratio, 2.472; 95% confidence interval, 1.096–5.576; P  = 0.029). Conclusions: Lack of response to conventional treatment for glucose management in acute IS is frequent and associated with poor outcomes. Abstract : Clickhere for the corresponding questions to this CME article.